A Pilot Study Investigating Changes in the Human Plasma and Urine NAD+ Metabolome During a 6 Hour Intravenous Infusion of NAD+ - Grant, Ross; Berg, Jade; Mestayer, Richard; Braidy, Nady; Bennett, James; Broom, Susan; Watson, James (Frontiers in Aging Neuroscience, 2019)
Accumulating evidence suggests that active maintenance of optimal levels of the essential pyridine nucleotide, nicotinamide adenine dinucleotide (NAD+) is beneficial in conditions of either increased NAD+ turnover or inadequate synthesis, including Alzheimer’s disease and other neurodegenerative disorders and the aging process. While studies have documented the efficacy of some NAD+ precursors such as nicotinamide riboside in raising plasma NAD+, no data are currently available on the fate of directly infused NAD+ in a human cohort. This study therefore documented changes in plasma and urine levels of NAD+ and its metabolites during and after a 6 hour 3 μmol/min NAD+ intravenous infusion. Surprisingly, no change in plasma [NAD+] or metabolites (nicotinamide, methylnicotinamide, ADP ribose and nicotinamide mononucleotide) were observed until after 2 hours. Increased urinary excretion of methylnicotinamide and NAD+ were detected at 6 hours, however no significant rise in urinary nicotinamide was observed. This study revealed for the first time that i) at an infusion rate of 3 μmol/min NAD+ is rapidly and completely removed from the plasma for at least the first 2 hours, ii) the profile of metabolites is consistent with NAD+ glycohydrolase and NAD+ pyrophosphatase activity and iii) urinary excretion products arising from an NAD+ infusion include NAD+ itself and meNAM but not NAM.